Chemical-physical characterization of complex systems: the case of pectins - Checchetti, Andrea; De Cindio, Bruno (My University, 2010)
In industrial process, separation of the hydrolyzed pectin solution is performed by centrifugal and filtration technologies. The effect of water addition to the hydrolyzed citrus peels slurry on the separation efficiency was investigated, with the aim to improve pectin recovery. Different dilution ratios were tested and it was found that the pectin recovery increases when increasing water addition passing through a maximum value. No relevant effects on pH and pectin yield were found when increasing the contact time between water and hydrolyzed slurry, confirming that no further progress of hydrolysis or extraction processes is caused by the dilution. Therefore, the increase in pectin recovery can be attributed only to the water addition. Intrinsic viscosity properties of commercial pectins and their mixtures in dilute solutions were investigated by using capillary viscometer. Influence of degree of esterification on interaction polymer-solvent was studied in order to provide additional evidence that can be used to elucidate the mechanism of the intermolecular interaction between two pectins and to determine their compatibility in dilute solutions. The viscosity measurements of ternary system have been performed by two techniques: 1. The first was determined by putting the polymer A and B with certain weight ratio in a pure solvent 2. The second was determined by putting the polymer A (referred to as guest or probe polymer) in solution in which the polymer B (referred to as host or matrix polymer) is found at a constant concentration. This technique is called the method of polymer solvent. By using the first method, two compatibility criteria, based on specific viscosity data and derived for synthetic polymers, have been applied to pectin mixtures at different degree of esterification (DE). Data revealed that positive molecular interaction take place when pectin in solution have a different DM (i.e. HM/LM mixtures), whilst an incompatible behavior was found for similar pectin (i.e. both HM and LM). In the case of incompatible pairs of pectin, also the apparent molecular weight of ternary solution showed an increase with respect to the additive mixing rule, due to repulsive forces. On the contrary, due to attractive forces in case of compatible pectin pairs, the molecular weight is lower than the calculated average. By using the polymer-solvent method, the coefficient (KAB) of interaction between polymers has been calculated. The analyzing of this parameter KAB allowed to justify the results obtained.
Dottorato di Ricerca in Ambiente, Salute e Processi Ecosostenibili Ciclo XXIII, a.a. 2007-2010
Keywords: Ingegneria chimica; Sistemi complessi; Pectine